Global pathways to education cultural spheres, networks, and international organizations - Martens, Kerstin 1974-; Windzio, Michael 1970- (Palgrave Macmillan, 2022)
In this open access volume, the editors identify the trajectories and patterns displayed by education systems and investigate the causes of change from a global and historical perspective. The contributors argue that the emergence and development of education systems can be traced back to inherent national factors, as well as to the international diffusion of ideas.The research presented in this volume is a wide-ranging analysis and explanation of the dynamics of emergence, diffusion, and change in relation to state education systems. The chapters offer an empirical investigation into whether the global diffusion of Western-rational educational content and organizational forms occurs as expected by neoinstitutionalist theory, or whether culturally specific developmental paths dominate in different parts of the world.The book will be of interest to students and researchers in various social science disciplines, including social policy, education, sociology, political science, international relations, organizational theory, and economics
Keywords: bicssc; bisacsh; Education and state; Educational sociology; Social policy; Bildungspolitik; Internationale Organisation; Internationale Politik; Hardcover, Softcover / Soziologie/Sonstiges; Aufsatzsammlung